Legal Protection for Rural Communities in Achieving Sustainable Food Land (A Case Study of Lamongan District, East Java) - Maulidah, Nur; Munir, Ahmad; Sholihan; Afiyah, Siti; Sundari, Ariefah (Manunggal Halim Jaya, 2025)
The sustainability of food land is crucial not only for economic productivity but also for maintaining ecological balance, cultural identity, and rural livelihoods. This study examines the effectiveness of legal protections for rural communities in safeguarding sustainable agricultural land, with a focus on Lamongan District, East Java. Using a normative-empirical approach, the research combines statutory analysis of agrarian laws with field surveys and interviews involving 256 respondents, including farmers, village officials, and legal experts. The findings reveal a persistent gap between legal norms and actual practices. Although Law No. 41/2009 on the Protection of Sustainable Agricultural Land and Law No. 5/1960 on Basic Agrarian Principles provide a strong legal foundation, enforcement is hindered by weak institutional coordination, low legal literacy, and limited authority at the village level. These challenges often result in land conversion without transparent procedures or adequate community participation, threatening both agrarian justice and national food security. The study underscores the need for participatory legal reforms, stronger intergovernmental coordination, and capacity-building initiatives for village institutions. The implications extend beyond Lamongan, offering insights for policymakers and scholars interested in land governance, food sovereignty, and rural sustainability. Future research should explore longitudinal and comparative perspectives to strengthen the integration of law and social policy in agrarian contexts.